Trapped in a glacial refugium: Phylogeography of the freshwater snail Melanopsis mingrelica (Mollusca, Gastropoda) in the Caucasus biodiversity hotspot - Ani Bikashvili; Levan Mumladze; Matthias Glaubrecht; Marco T. Neiber (Zoologica Scripta, 2025)
The Western Caucasus is considered a refugium for several freshwater invertebrates, but detailed phylogeographic studies are lacking. By using mitochondrial sequence data, amplified fragment length polymorphisms and distribution modelling, we study the phylogeography of the Caucasian freshwater snail Melanopsis mingrelica Mousson, 1863, and discuss the role of the Western Caucasus region as a glacial refugium. Volcanism in the Lesser Caucasus and the formation of highlands to its south in the Late Miocene and Pliocene may have effectively trapped the lineage leading to the freshwater snail M. mingrelica in the western Georgian Colchis region after its arrival there during in the Late Miocene or Early Pliocene. Our results show that the Western Caucasus region can be considered a refugium for a Melanopsis lineage at the northern margin of the range of a genus that today is otherwise mostly adapted to relatively warm climatic conditions. Our results further show that the Western Caucasus region served as a large and homogeneous refugium for M. mingrelica and that global warming may have facilitated the colonization of the Caspian Sea drainage basin by M. mingrelica .